1993
DOI: 10.1288/00005537-199310000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Determining the site of airway collapse in obstructive sleep apnea with airway pressure monitoring

Abstract: Twenty patients with obstructive sleep apnea (OSA) underwent complete polysomnography and simultaneous upper airway pressure monitoring with a custom-made, soft silicone-covered catheter measuring 2.3 mm in diameter. The catheter had four solid-state microtip pressure sensors positioned in the posterior nasopharynx, immediately caudal to the tip of the uvula, at the level of the hyoid bone, and in the midesophagus. The level(s) of airway collapse was determined by changes in the pressure patterns between trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 3 publications
2
32
0
3
Order By: Relevance
“…In the study by SHEPARD and THAWLEY [5], oropharyngeal collapse is said to occur when pressure deflections are absent in two sensors: one located in the nasopharynx at the level of the soft palate and the other located just distal to the inferior margin of the soft palate, at the base of tongue. By contrast, in the study by KATSANTONIS et al [15], collapse of the oropharyngeal segment is defined as absence of pressure deflections in a sensor located at the posterior choanae. What is defined as nasopharyngeal collapse in our present study corresponds to the oropharyngeal collapse in the study of KATSANTONIS et al [15], and our definition of oropharyngeal collapse agrees with the definition of oropharyngeal collapse used by SHEPARD and THAWLEY [5].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In the study by SHEPARD and THAWLEY [5], oropharyngeal collapse is said to occur when pressure deflections are absent in two sensors: one located in the nasopharynx at the level of the soft palate and the other located just distal to the inferior margin of the soft palate, at the base of tongue. By contrast, in the study by KATSANTONIS et al [15], collapse of the oropharyngeal segment is defined as absence of pressure deflections in a sensor located at the posterior choanae. What is defined as nasopharyngeal collapse in our present study corresponds to the oropharyngeal collapse in the study of KATSANTONIS et al [15], and our definition of oropharyngeal collapse agrees with the definition of oropharyngeal collapse used by SHEPARD and THAWLEY [5].…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, in the study by KATSANTONIS et al [15], collapse of the oropharyngeal segment is defined as absence of pressure deflections in a sensor located at the posterior choanae. What is defined as nasopharyngeal collapse in our present study corresponds to the oropharyngeal collapse in the study of KATSANTONIS et al [15], and our definition of oropharyngeal collapse agrees with the definition of oropharyngeal collapse used by SHEPARD and THAWLEY [5]. The use of different definitions for the UA emphasizes the need for a consensus at this point.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Many studies have demonstrated that the airway is anatomically smaller in snorers and OSAS patients. In many studies, the most affected area in patients with sleep apnea is the retropalatal region of the oropharynx [8][9][10] . It is stated in the study of Ahn et al one of the reasons of narrowness in retropalatal area was increase in volume of tongue 11 .…”
Section: Discussionmentioning
confidence: 99%